ANALISIS KESESUIAN SARANA DAN PRASARANA PRAKTIKUM KOMPETENSI KEAHLIAN TEKNIK KENDARAAN RINGAN DI SMK NEGERI 2 PANDEGLANG: ANALISIS KESESUIAN SARANA DAN PRASARANA PRAKTIKUM KOMPETENSI KEAHLIAN TEKNIK KENDARAAN RINGAN DI SMK NEGERI 2 PANDEGLANG - Prasstiawan, Sahrul; Atep Iman; Ricky Cahyasari Putra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Vocational education is required to produce competent and work-ready graduates, so the availability of adequate practicum facilities and infrastructure is the main key. This study aims to analyze the level of suitability of practicum facilities and infrastructure for Light Vehicle Engineering Expertise Competence (TKR) at SMK Negeri 2 Pandeglang. This analysis refers to three main standards, namely Permendikbud Number 34 of 2018, the Indonesian National Work Competency Standards (SKKNI) Level II in the automotive sector, and the application of Occupational Health and Safety (K3) principles. The study used a mixed methods approach with an explanatory sequential design. Quantitative data were obtained through a four-point Likert scale questionnaire, observation, and documentation, then deepened with qualitative data through interviews with productive teachers and workshop heads. The results showed that the level of suitability of practicum facilities reached 72% and practicum infrastructure was 73.21%, which is included in the fairlyappropriate category. However, significant limitations remain in the availability of modern technology-based practical tools, the ratio of tools to the number of students, the layout of the workshop space, and the suboptimal implementation of K3, particularly regarding the availability of Personal Protective Equipment (PPE) and safety signs. These findings indicate that the TKR practical facilities and infrastructure at SMK Negeri 2 Pandeglang do not fully meet national standards and work competency requirements.